2010
DOI: 10.1002/jssc.200900466
|View full text |Cite
|
Sign up to set email alerts
|

Zeta potential determination as a new way of stationary phases characterization for liquid chromatography

Abstract: A set of seven homemade octadecyl silica-based bonded phases was investigated. Their zeta potential data in methanol and ACN as well as in methanol-water and ACN-water solution were obtained using Zetasizer. The influence of both the coverage density of bonded ligands and the end-capping of the modified surface on these data was investigated. Presented results may give useful information about the accessibility of the residual silanols in different mobile phases during the chromatographic analysis. Those measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…A series of polar stationary phases provide positive values of the zeta potential in the present of the solvent with hydroxyl groups (methanol or water) whereas in the case of ACN the zeta potential is negative. It confirms the observation [4], that solvation process influence significantly zeta potential of the stationary phases in RP conditions. Usually, ACN causes values that are more negative whereas the presence of methanol moves these values to a positive range.…”
Section: Resultssupporting
confidence: 91%
“…A series of polar stationary phases provide positive values of the zeta potential in the present of the solvent with hydroxyl groups (methanol or water) whereas in the case of ACN the zeta potential is negative. It confirms the observation [4], that solvation process influence significantly zeta potential of the stationary phases in RP conditions. Usually, ACN causes values that are more negative whereas the presence of methanol moves these values to a positive range.…”
Section: Resultssupporting
confidence: 91%
“…Positive charges attracted by the field create the second layer of the electric double layer (Fig. 5) [81].
Fig.
…”
Section: Separation Mechanism In Hilic Modementioning
confidence: 99%
“…Many different and novel approaches to the study of the retention mechanism in HPLC may be found in the literature [11][12][13]. One of them is the determination of zeta potential [14]. It denotes the surface charge that occurs in the presence of an aqueous solution, when functional groups dissociate on hydrophilic surface or negative ions adsorb onto hydrophobic surfaces from the solution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pH of the solution, other parameters e.g. type of salt and its concentration are also very influential when surface electric charges are considered [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%